2009
DOI: 10.2165/00148581-200911030-00004
|View full text |Cite
|
Sign up to set email alerts
|

Current Pharmacological Management of Gastro-Esophageal Reflux in Children

Abstract: Gastro-esophageal reflux (GER) is a common phenomenon, characterized by the regurgitation of the gastric contents into the esophagus. Gastro-esophageal reflux disease (GERD) is the term applied when GER is associated with sequelae or faltering growth. The main aims of treatment are to alleviate symptoms, promote normal growth, and prevent complications. Medical treatments for children include (i) altering the viscosity of the feeds with alginates; (ii) altering the gastric pH with antacids, histamine H(2) rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(56 citation statements)
references
References 65 publications
1
55
0
Order By: Relevance
“…PPI therapy is proven effective for healing esophagitis in adults (13)(14)(15), for reducing acid exposure in infants (16)(17)(18) and is suggested to heal erosive esophagitis in 89% of children (19). However PPIs have not been proven to relieve symptoms of GERD in infants (20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%
“…PPI therapy is proven effective for healing esophagitis in adults (13)(14)(15), for reducing acid exposure in infants (16)(17)(18) and is suggested to heal erosive esophagitis in 89% of children (19). However PPIs have not been proven to relieve symptoms of GERD in infants (20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%
“…A meta-analysis by Tighe et al reported that ranitidine and omeprazole are safe and effective medications which promote symptomatic relief and histological evidence of benefit in infant with GERD 11. However no similar studies have been conducted in preterm babies.…”
Section: Commentarymentioning
confidence: 99%
“…The most commonly reported adverse event was diarrhea. Two systematic reviews of pediatric GERD treatments did not recommend the use of domperidone in this patient population due to lack of data showing its ef fi cacy [ 7,8 ] . Oral domperidone in neonates is associated with prolonged QTc interval in patients ³ 32 weeks of gestation [ 9 ] .…”
Section: Dopamine-2 (D2) Receptor Antagonists Domperidonementioning
confidence: 99%